Фреквенција на ХЛА хаплотиповите во Република Македонија и нивната улога при трансплантација на матични клетки - Киријас, Мери (Медицински факултет, УКИМ, Скопје, 2018)
Introduction: The gene complex that codes for the Human Leucocyte Antigens (HLA) located on the short arm of chromosome 6, are the most polymorphic genes in the human genome. The complexity of HLA polymorphism is due to the high number of gene loci, a lot of alleles in the loci and the combination of their products. Analysis of HLA polymorphism and linkage disequilibrium between alleles, as well as the difference in frequency of HLA alleles and haplotypes between populations has an application in the search of a donor for hematopoietic stem cell transplantation and in association studies of HLA in the pathogenesis of diseases. Few studies are published so far for the polymorphisms of some HLA loci in the Macedonian population. It imposed the need for determination of the frequency of HLA-A, -B, -C and -DRB1 allele groups and haplotypes in the Macedonian population. The knowledge of these frequencies would shorten the time necessary for the search of compatible donor and stem cell transplantation. Moreover, the analysis of HLA polymorphism in healthy Macedonian population would help in determining the relative risk of alleles and different diseases. Aim of the study: The main aim of this study is to determine the frequency of HLA allele groups and haplotypes in the Macedonian population, in a sample with defined haplotypes and to calculate the degree of genetic similarity with other population. Moreover, the aim is to determine the HLA profile of the donors in the Macedonian Bone Marrow Donor Registry (MBMDR). Material and Methods: This study is performed in 2 groups of participants. Group 1 is 286 healthy individuals, parents of the patients sent to the Institute of Immunobiology and Human Genetics for HLA typing. They have defined haplotypes due to known family history. Group 2 are the 1541 volunteer donors in MBMDR, divided in three groups Macedonians, Albanians and Macedonian Muslims. In both groups we calculated the allele frequency (HLA-A, HLA-B, HLA-C and HLA-DRB1) and 4-loci haplotypes, and a group of 566 individuals was also typed for HLA-DQ. Typing is performed with HLA-DNA intermedium resolution. DNA is isolated with the phenol-chlorophorm method of isolation and with the automated machine Duplica Prep, EuroClone. HLA typing was performed with two methods: method of reverse line strip (RLS) from INNOGENETICS, Belgium and SSO from One Lambda, USA. Allele group frequency, 2-, 3-, 4- and 6-loci haplotypes, as well as Hardy-Weinberg equilibrium was calculated with the software Arlequin3.5. The Macedonian population was compared with 30 European and world population with the software Phylip. Dendrogram was constructed using the values for Nei’s genetic distance calculated for HLA-A, -B and -DRB1 loci. Linkage disequilibrium (D’) for two loci haplotypes was calculated in the Arlequin3.5 software. Results: We identified 18 HLA-A, 26 HLA-B, 13 HLA-C and 13 HLA-DRB1 allele groups in group 1. The most frequent allele groups with frequency >10 % were HLA-A*02 (29,0 %), HLA-A*24 (13,8 %), HLA-B*35 (16,1 %), HLA-B*51 (14,7 %), HLA-B*18 (14, 7 %), HLA-C*07 (27,9 %), HLA-DRB1*11 (25,5 %) and HLA-DRB1*16 (14,8 %). The most frequent 4 loci haplotypes were HLA-A*01-B*08-C*07-DRB1*03 (2,7 %), HLA-A*02-B*18-C*07-DRB1*11 (2,6 %), HLA-A*24-B*35-C*04-DRB1*11 (1,5 %) and HLA-A*24-B*18-C*07-DRB1*11 (1,3 %). We detected in MBMDR 59 allele groups in class I and 13 in class II in Macedonians, 51 in class I and 12 in class II in Albanians and 46 in class I and 12 in class II in Macedonian Muslims. Most common haplotype in Albanians and Macedonian Muslims is HLA-A*02-B*18-C*07-DRB1*11 (4,6 % and 6, 8 %). The most frequent HLA-DQA1 allele groups in the Macedonian population were HLA-DQA1*01 (49,7 %) and HLA-DQA1*05 (33,9 %), and in HLA-DQB1 locus HLA-DQB1*05 (34,6 %) and HLA-DQB1*03 (33,5 %). The most common 6-loci haplotype in Macedonians is HLA-A*02-B*18-C*07-DRB1*11-DQA1*05-DRB1*03 (4,2 %). The Macedonian population has the most similarities with the populations from Balkan Peninsula. Conclusion: The results from this study for the first time show the frequency of HLA-A-B-C-DRB1 haplotypes in the Macedonian population with defined haplotypes. We also determined the HLA profile of the volunteer donors from the MBMDR and the degree of genetic distance of the Macedonian population with other populations. This data can be used for further planning of strategies for donor requirement and as a control group in association studies for different diseases.
Frequency of HLA haplotypes in Republic of Macedonia and their role in stem cell transplantation
Докторска дисертација одбранета во 2018 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Соња Генадиева Ставриќ.
Keywords: HLA; HLA haplotypes; polymorphism; Macedonian Bone Marrow Donor Registry; population study